Adaptações cardiovasculares ao longo de 11 semanas de treinamento muscular inspiratório em ciclistas recreacionais: estudo clínico randomizado controlado e duplo-cego - Silva, Claudio Donisete da (2019)
Background: The cardiovascular variables [heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP) and rate pressure product (RPP)] are important parameter for the determination of the ideal intensity of training. However, there are no studies that evaluate the same variables during the inspiratory muscle training. Thus, the objective of this study was to evaluate the response of cardiovascular variables HR, SBP, DBP and RPP during 33 sessions and in different intensities of inspiratory muscle training in recreational cyclist. Methods: Thirty-one men, recreational cyclists, between 20 and 40 years old, were stratified randomized in three training groups: low [Sham Group (SG)], moderate [60% of MIP (60G)] and high intensity [Critical Inspiratory pressure (CPG)]. All groups performed: inspiratory muscle strength test and incremental inspiratory muscle endurance test, to determinate load. Training program was conducted during 11 weeks, three times a week, during approximately 55 minutes/session. HR was recorded before, during and after each training session and SBP and DBP was recorded before and after each session, RPP was calculated by multiplying HR by SBP before and after each session. For statistical analysis the Two-way mixed ANOVA was used and post-hoc analysis was conducted by Tukey test. The level of significance was set at p <0.05. Results: The deltas of HR and RPP values were higher in 60G and CPG, when compared to SG, suggesting greater cardiac demand. On the other hand, the delta of SBP presented lower SG values compared to 60G and CPG. Regarding the weeks of training, there was a reduction of SBP in the fifth and ninth weeks of the experimental protocol when compared to the first training week. DBP presented difference only between SG and CPG. Conclusion: Inspiratory muscle training was not able to reduce cardiovascular variables over 11 weeks, at each training session, in recreational cyclists although higher loads led to greater demands.